Odpornost betona z dodatkom reciklirane gume proti zmrzovanju in tajanju - Jelušič, Primož (Gradbeni vestnik, 2013)
Scrap tires and fly ash are being generated and accumulated in large volumes causing an increasing threat to the environment. There are mechanical, environmental and economic reasons to include recycled rubber and fly ash in concrete mixture. The concrete mixture with recycled rubber and fly ash is presented. Concrete used in foundations of non-load bearing structures should be a minimum strength classification of C12/15. In the paper, the freeze-thaw resistance of rubber included concrete with fly ash were investigated. Rubber included concrete is not freeze-thaw resistant, without entrained air.
Keywords: aerant; air-entrainer; beton; concrete; elektrofiltrski pepel; fly ash; lastnosti; properties; reciklirana guma; recycled rubber